2024
DOI: 10.3393/ac.2023.00094.0013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcomes after high and low ligations with lymph node dissection around the root of the inferior mesenteric artery in patients with rectal cancer

Min Wan Lee,
Sung Sil Park,
Kiho You
et al.

Abstract: Purpose: This study aimed to evaluate the long-term clinical outcomes based on the ligation level of the inferior mesenteric artery (IMA) in patients with rectal cancer.Methods: This was a retrospective analysis of a prospectively collected database that included all patients who underwent elective low anterior resection for rectal cancer between January 2013 and December 2019. The clinical outcomes included oncological outcomes, postoperative complications, and functional outcomes. The oncological outcomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Given the recurrence locations in the low ligation group, the authors proposed that high ligation might be a safer oncological procedure. However, Lee et al [4] reported no differences in 5-year OS and RFS between the high and low IMA ligation groups in their recent study. Other research has similarly failed to demonstrate oncological benefits associated with high ligation of the IMA.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…Given the recurrence locations in the low ligation group, the authors proposed that high ligation might be a safer oncological procedure. However, Lee et al [4] reported no differences in 5-year OS and RFS between the high and low IMA ligation groups in their recent study. Other research has similarly failed to demonstrate oncological benefits associated with high ligation of the IMA.…”
mentioning
confidence: 84%
“…However, no significant differences were observed between the groups in terms of the number of harvested LNs, LN metastasis, 5-year mortality rate, 5-year disease-free survival rate, duration of surgery, intraoperative blood loss, or postoperative ileus. Lee et al [4] also reported no difference in AL rates between high and low ligation; similarly, an RCT by Fujii et al [7] involving 331 patients found no differences in AL rates between the 2 ligation techniques. Since AL is a potentially life-threatening surgical complication, a larger, multicenter RCT is essential to resolve these conflicting findings.…”
mentioning
confidence: 91%
See 3 more Smart Citations